O texto literário capital cultural no ensino / aprendizagem de francês língua estrangeira - Catharina, Pedro Paulo Garcia Ferreira (1995)
This dissertation has the purpose of rethinking the importance of the literary text in the process of teaching / leaming French as a Foreign Language. It regards the literary text as being an authentic document which is often overlooked in didatic activities devised for teaching French to foreigners. It looks into the approach to the text by French as a Foreign Language methodologies which favour an approach to either oral or written discourses. It also reviews Linguistic, Pragmatic and Discourse Analysis studies that have i fluenced the making of didatic materiais. It then submits the literary text as a didatic material capable of promoting the development of literacy in French as a Foreign Language. Finally, from a sociological standpoint, which is closely related to teaching policies, this dissertation sees the literary text as an important cultural asset for the leamer' s induction into the cutural universe he/she wishes to enter and shows how the literary text is markedly present in the French habitus.